Pilot study of attentional retraining for postpartum smoking relapse - Forray, Ariadna; Gunter-Riley, R. Gwen; Maltz, Caro; Waters, Andrew J. (Frontiers in Psychiatry, 2023)
Introduction: Tobacco smoking is a leading cause of preventable death worldwide. The perinatal period provides a unique opportunity for intervention, as many smokers quit smoking during pregnancy but relapse postpartum. Novel relapse prevention interventions that reduce the burden of treatment attendance in this population are needed. Attentional retraining (AR) has been shown to reduce attentional biases towards smoking-related stimuli, a cognitive process implicated in smoking, AR has not been applied to perinatal smokers, and the effect of AR on craving and smoking is not clear. The goal of this study was to evaluate the delivery of AR for smoking cues in perinatal smokers utilizing a mobile intervention.Methods: This pilot study utilized Ecological Momentary Assessment (EMA) methodology delivered on a mobile device to examine the relapse process and evaluate the utility of AR in former smokers attempting to remain abstinent postpartum. AR (or Control Training) was administered to abstinent smokers (N=17) for up to two weeks both before and after delivery.All 17 participants completed the study. There was evidence that AR reduced attentional bias in the AR group (vs. Controls). There was no evidence that AR reduced craving.An exploratory analysis revealed that there was no evidence that AR reduced smoking during the study period. Discussion: AR using EMA methodology via a mobile device is feasible in perinatal smokers.Further research using larger samples is required to evaluate the utility of mobile AR in reducing craving and smoking.